Kinetic modeling and simulation of non-solvent induced phase separation: Immersion precipitation of PVC-based casting solution in a finite salt coagulation bath. (11th June 2020) - Ahmad, Tausif; Guria, Chandan; Mandal, Ajay
Abstract: A mathematical model is developed to describe the phase inversion kinetics for the fabrication of porous PVC-based polymeric membranes under finite coagulation bath condition. The model accounts for the non-quasi-stationary diffusion of non-solvent across the solidified membrane, time-variant non-solvent concentration in the coagulation bath and swelling of the membrane while phase inversion. An analytical solution is obtained for the pseudo-steady-state model, whereas the unsteady-state phase inversion model is converted by finite integral transform to a set of first-order coupled ordinary differential equations, which are solved by the numerical means. The above models are tested with the real-time movement of the solidification front using PVC/N-methyl pyrrolidine (NMP)-based casting solution involving Pluronic F127 and bentonite additives, and CaCl2, NaCl and KCl salt coagulation bath as well as demineralized water. The proposed pseudo-steady-state and unsteady phase inversion models predict diffusivity of the non-solvent through membrane matrix and the diffusivity follows the following order for a given casting solution: KCl > NaCl > CaCl2 > water. The results reveal that the combined effect of Pluronic F127 and bentonite in PVC-NMP-based casting solution dominates over individual additives and it results from the higher non-solvent diffusivity with fast liquid-liquid demixing as well as the enhancement in membrane swelling. Graphical abstract: Image 1 Highlights: Phase inversion kinetic model is developed for the polymeric membrane fabrication. Model accounts finite coagulation, swelling and steady- and unsteady-state behavior. Finite integral transform and numerical methods are used for unsteady-state model. Models are validated using a PVC-based casting solution and salt coagulation bath. Model-experiments are proposed to measure the real-time solidification moving front.